Enhanced photovoltaic performance using biomass derived nano 3D ZnO hierarchical superstructures and a D−A type CS-Symmetric triphenylamine linked bisthiazole. (1st January 2018) - Ansari, Mohammad Shaad; Maragani, Ramesh; Banik, Avishek; Misra, Rajneesh; Qureshi, Mohammad
Abstract: Herein, a facile one step hydrothermal route for the controlled, biomass assisted synthesis of three dimensional (3D) Zinc oxide (ZnO) hierarchical superstructures (HSs), assembled with compacted ZnO nanorods (NRs) is reported. Anionic polysaccharide "Polygalacturonic acid" is utilized as a crystal growth modifier for assembling the basic building blocks (ZnO NRs). Probable mechanism for the formation of superstructures through the interaction between the polysaccharide and ZnO growth units is discussed. Photovoltaic properties of as-synthesized 3D ZnO HSs as compared to its basic structural unit i.e., ZnO NRs are investigated by sensitizing with a bisthiazole linked metal free donor-acceptor dye; D1. A substantial enhancement (∼35%) in efficiency (η) for 3D ZnO HSs based device (η ≈ 5.37%) as compare to ZnO NRs (η ≈ 3.48%) is being observed, mainly due to better charge separation and collection, owing to a superior electron transport ability of compacted building blocks, better light-scattering effect, higher BET surface area for sensitizer loading and efficient electron injection from dye D1 to the ZnO. Electrochemical impedance spectroscopic (EIS) analysis is carried out to support a slower photogenerated electron-hole recombination rate and better charge transports in the 3D ZnO HSs based photovoltaic device. Graphical abstract: Highlights: Polygalacturonic acid assisted synthesis of 3D ZnO/1D ZnO NRs superstructures. Formation mechanism of superstructures divulged the role of bio-template and base. 3D ZnO Superstructures based devices are furnishing the efficiency of about ∼5.4%. D-A dye for understanding charge injection process having multiple anchoring groups. Enhanced efficacy due to large surface area and better charge transfer kinetics.